The Maudsley Prescribing Guidelines in Psychiatry - Taylor, David, 1963-; Barnes, Thomas R. E; Young, Allan H. (Hoboken : John Wiley & Sons, 2021)
"This 14th edition of The Guidelines has been written under extraordinary circumstances: the coronavirus pandemic. This global phenomenon has radically altered the lives and working practices of billions of people and most of us are now familiar, either personally or vicariously, with the experience of the serious physical illness that is associated with COVID-19. Those working in healthcare have been particularly grievously affected, caring for those made ill by the disease while risking infection themselves. In this environment, the writing of a book has an extremely low priority, if any at all. It is in this context that I give boundless and sincere thanks to all those who have contributed to this edition of The Guidelines under such challenging conditions. Of course, mental health problems have not gone away during the pandemic, and the optimal treatment of mental illness remains a vital imperative. This objective will be all the more critical as we come to deal with the mental health consequences of the pandemic"--
Keywords: Psychopharmacology; Drugs -- Prescribing